2021
DOI: 10.1177/01427237211026435
|View full text |Cite
|
Sign up to set email alerts
|

Exploring influential factors of shape classifier comprehension and production in Mandarin-speaking children

Abstract: Mandarin classifiers are a complex system, but little is known about how Mandarin-speaking children manage to learn the system. Based on the extant literature, we explored potential factors influencing the comprehension and production of Mandarin shape classifiers, including classifier-based semantic categorization and errors pertaining to the semantic strategies, input frequency of classifier-noun combinations, and vocabulary knowledge. In total, 138 typically developing monolingual Mandarin-speaking children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
2
2
1
Order By: Relevance
“…In summary, the most common non-target responses made by children are omissions of classifiers (NC; counting items with bare numerals), followed by substitutions with general classifiers (GC) and, then, use of incorrect classifiers (WC). This finding is in contrast with other studies finding omissions of classifiers to be rare even among younger Japanese and Chinese children (Hao et al, 2021;Uchida & Imai, 1999). Such discrepancies may be affected by the inclusion of nonce items in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In summary, the most common non-target responses made by children are omissions of classifiers (NC; counting items with bare numerals), followed by substitutions with general classifiers (GC) and, then, use of incorrect classifiers (WC). This finding is in contrast with other studies finding omissions of classifiers to be rare even among younger Japanese and Chinese children (Hao et al, 2021;Uchida & Imai, 1999). Such discrepancies may be affected by the inclusion of nonce items in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…To begin with, there are very few studies that examine comprehension and production of classifiers in child development. The most recent study (Hao et al, 2021) found a significant gap between comprehension and production accuracy of classifiers in Mandarin-speaking children, corroborating the findings of previous studies (Chien et al, 2003;Uchida & Imai, 1999) that comprehension precedes production in classifier acquisition. Among those studies that examine comprehension of classifiers, children seem to reach ceiling (over 90% accuracy) on various types of sortal classifiers by age six, with significant improvements between four to five years of age (Japanese: Uchida & Imai, 1996, 1999Sumiya & Colunga, 2006;Yamamoto & Keil, 2000, Chinese: Chien at al., 2003Li et al, 2010;Hao et al, 2021).…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations